Trade Imbalances and the Political Economy of a Transitional Fund in the EAC - Rasul Shams (Hamburg Institute of International Economics (HWWA), 2003)
The EAC is on the verge of establishing a customs union. But this is accompanied by fears that the Customs Union would lead to trade imbalances among the Partner States, which would create serious problems for the proper functioning of the Customs Union itself. To mitigate these problems the establishment of a transitional fund is proposed. Based on a study of the trade effects of the Customs Union it is shown that these fears are unfounded, and the establishment of a transitional fund to address imbalances therefore not necessary. Stakeholders views on the establishment of a transitional fund are also analysed to assess their influence on the integration policy in the EAC. The historical background of the fears of a customs union is described and it is shown how these fears continue to present time, in spite of changing economic conditions.
Keywords: F15; O55; P16; 330; Economic Integration; Africa; Political Economy; Zollunion; Handelsbilanz; Zahlungsbilanzungleichgewicht; Wirtschaftsintegration; Public Choice; Ostafrika